1994
DOI: 10.1055/s-2008-1045489
|View full text |Cite
|
Sign up to set email alerts
|

Orbitametastase eines Nierenkarzinoms

Abstract: The in toto excision of an orbital metastasis of a renal cell carcinoma is a valid therapeutic approach regarding the tumor morphology and the achievable postoperative symptomatic relief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Carcinomas of the breast 1,2 and the bronchial system are the most common sites of origin, 3-6 but there are also descriptions of choroidal melanoma, 7-9 retinoblastoma, 10 liposarcoma, 11 cutaneous melanoma, 12 hepatocellular carcinoma, 13-16 carcinoma of the cervix, 17,18 leiomyosarcoma, 19 urachal tumor, 20 Ewing's sarcoma, 21,22 angiosarcoma, 23 renal cell carcinoma, 24,25 adenocarcinoma of the salivary gland, 26 thymic car- cinoma, 27 transitional cell carcinoma of the bladder, 28,29 pleural mesothelioma 30 and carcinoid 31-36 as primary neoplasms. The metastasis of a carcinoid tumor of the intestinal tract was the most uncommon tumor in our group.…”
Section: Resultsmentioning
confidence: 97%
“…Carcinomas of the breast 1,2 and the bronchial system are the most common sites of origin, 3-6 but there are also descriptions of choroidal melanoma, 7-9 retinoblastoma, 10 liposarcoma, 11 cutaneous melanoma, 12 hepatocellular carcinoma, 13-16 carcinoma of the cervix, 17,18 leiomyosarcoma, 19 urachal tumor, 20 Ewing's sarcoma, 21,22 angiosarcoma, 23 renal cell carcinoma, 24,25 adenocarcinoma of the salivary gland, 26 thymic car- cinoma, 27 transitional cell carcinoma of the bladder, 28,29 pleural mesothelioma 30 and carcinoid 31-36 as primary neoplasms. The metastasis of a carcinoid tumor of the intestinal tract was the most uncommon tumor in our group.…”
Section: Resultsmentioning
confidence: 97%
“…Kinderman et al [4] presented a patient with eyelid metastasis as the first manifestation of a renal cell carcinoma. Schmidt et al [5] reported a renal cell cancer metastatic to the eyelid that recurred after excision. The clinical picture of a ‘recurrent chalazion’ and clear cell features on histopathology are typically suspicious of a sebaceous gland carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…At the time of the second CT scan, the suspicion of orbital metastasis was founded on the fact that both kidney and breast tumours can give rise to secondary orbital localisations presenting as Tolosa-Hunt syndrome [19,20,21,22,23,24]. …”
Section: Discussionmentioning
confidence: 99%